2012
DOI: 10.1038/jcbfm.2012.50
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia and the Quantitative Evaluation of Neurovascular Coupling

Abstract: Anesthesia has broad actions that include changing neuronal excitability, vascular reactivity, and other baseline physiologies and eventually modifies the neurovascular coupling relationship. Here, we review the effects of anesthesia on the spatial propagation, temporal dynamics, and quantitative relationship between the neural and vascular responses to cortical stimulation. Previous studies have shown that the onset latency of evoked cerebral blood flow (CBF) changes is relatively consistent across anesthesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
195
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(200 citation statements)
references
References 165 publications
(110 reference statements)
3
195
0
2
Order By: Relevance
“…This could be a consequence of anesthesia, which strongly dampens the HRF. 36,38 Also, we show here that stimulusevoked ringing has substantial site-to-site variations in frequency, so the ringing would be masked to spatially averaged measurements such as laser speckle or Doppler flowmetry. 31,39 Regardless, our model is also capable of fitting non-oscillatory flow responses using the overdamped form of the FEW impulse response.…”
Section: Discussionmentioning
confidence: 71%
“…This could be a consequence of anesthesia, which strongly dampens the HRF. 36,38 Also, we show here that stimulusevoked ringing has substantial site-to-site variations in frequency, so the ringing would be masked to spatially averaged measurements such as laser speckle or Doppler flowmetry. 31,39 Regardless, our model is also capable of fitting non-oscillatory flow responses using the overdamped form of the FEW impulse response.…”
Section: Discussionmentioning
confidence: 71%
“…Assuming ␣-chloralose has the same effect, it is possible that astrocytic calcium signaling is affected under the anesthetic conditions used in this study. While anesthesia is known to have an impact on the magnitude of the evoked BOLD responses (Franceschini et al, 2010;Masamoto and Kanno, 2012), neurovascular coupling has been found to be robustly maintained when ␣-chloralose is used to maintain general anesthesia (Ueki et al, 1992;Masamoto and Kanno, 2012). In the present study we demonstrate release of ATP (primary signaling molecule of astrocytes), BOLD fMRI responses and intact cerebrovascular responses to CO 2 in the somatosensory cortex of ␣-chloralose-anesthetized rats allowing study of the fundamental mechanisms underlying the role of astrocytes in the mechanisms of neurovascular coupling.…”
Section: Limitationsmentioning
confidence: 99%
“…36,37 Urethane, another widely used anesthetic, minimally affects cardiovascular, respiratory, and spinal reflexes, providing long-term stability and balanced actions on multiple neurotransmitter receptors. 38 Hence, a-chloralose or urethane was suitably used with urethane preferred for the relatively longer fLDI and fMRI experiments. As similar evoked potentials and neuronal-hemodynamic coupling exist between a-chloralose and urethane anesthesia, 39 there were no major anesthetic confounds affecting the results.…”
Section: Surgical Preparationmentioning
confidence: 99%